Edukasi Waspada Terkena Ispa Pada Musim Hujan Di Masa Pandemi Di Smp Salafiyah Darul Falah Pagutan Kota Mataram - Hapipah, Hapipah; Istianah, Istianah; Hadi, Irwan; Apriani Idris, Baiq Nurainun (Stikes Yarsi Mataram, 2021)
Acute Respiratory Tract Infection (ISPA) is the leading cause of morbidity and mortality of infectious diseases in the world. Nearly four million people die from ISPA each year, 98% caused by lower respiratory tract infections, and mortality rates are very high in infants, children, and the elderly. One of the causes of the high incidence of ISPA is due to lack of knowledge about ISPA. This can be due to lack of socialization about ISPA, how to prevent ISPA, and how to deal with ISPA. One of the things that can be done to increase knowledge is to provide health education about ISPA. This community service aims to provide education about ISPA disease in the rainy season during the pandemic at Smp Salafiyah Darul Falah Pagutan Mataram City. This activity was attended by 47 students using LCD Projector and leaflets. The method used is by lectures, discussions and practices how to wash hands properly and conduct pre tests and post tests. pretest results of students' level of knowledge about ISPA the most knowledge is less than 24 people (51.0%) while after being given education in the form of health counseling, there was an increase in participants' knowledge to a sufficient level of knowledge as many as 25 people (53.2%). It is hoped that this community service activity can be useful for Smp Salafiyah Darul Falah Pagutan Mataram City.